2018
DOI: 10.1111/nicc.12379
|View full text |Cite
|
Sign up to set email alerts
|

Intensive care nurse conceptions of well‐being: a prototype analysis

Abstract: Intensive care nurse conceptions of work well-being are fundamental for future measures of work well-being and future interventional studies and initiatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(54 citation statements)
references
References 28 publications
4
50
0
Order By: Relevance
“…The facets were named using adjectives to support them becoming ICU mission statements, such as “our ICU is healthy , authentic , meaningful , connected and innovative .” These facets scaffold the integration of the empirical and ICU nurse perspectives from the findings of this programme of research. The ICU nurse work well‐being characteristics and their strengtheners were re‐analysed and sorted according to the five facets and then reported alphabetically (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The facets were named using adjectives to support them becoming ICU mission statements, such as “our ICU is healthy , authentic , meaningful , connected and innovative .” These facets scaffold the integration of the empirical and ICU nurse perspectives from the findings of this programme of research. The ICU nurse work well‐being characteristics and their strengtheners were re‐analysed and sorted according to the five facets and then reported alphabetically (Table ).…”
Section: Resultsmentioning
confidence: 99%
“… Note : This table reports re‐analysed data including ICU nurse‐identified work well‐being characteristics and strengtheners; superscript “A” denotes an actual strengthener, superscript “P” denotes a potential strengthener.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A need for research to identify strategies to enhance psychological well‐being has been identified (Ministry of Health, ; Smith & Hollinger‐Smith, ). Studies exploring how older adults perceive well‐being, that is what well‐being means and which aspects are important, can provide insight into the multi‐dimensional nature of the concept (Douma, Steverink, Hutter, & Meijering, ; Jarden, Sandham, Siegert, & Koziol‐McLain, ). That older adults may respond to different interventions to enhance their well‐being is also acknowledged (Smith & Smith, ).…”
Section: Introductionmentioning
confidence: 99%